2023
DOI: 10.1111/jerd.13132
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of 3D‐printed and milled composite resins for definitive restorations: An in vitro comparison of initial strength and fatigue behavior

Elisabeth Prause,
Tine Malgaj,
Andraž Kocjan
et al.

Abstract: ObjectiveTo evaluate the flexural strength and fatigue behavior of a novel 3D‐printed composite resin for definitive restorations.Materials and MethodsFifty disc‐shaped specimens were manufactured from each of a nanohybrid composite resin (NHC), polymer‐infiltrated ceramic network (PICN), and 3D‐printed composite resin (3D) with CAD‐CAM technology. Biaxial flexural strength (σin) (n = 30 per group) and biaxial flexural fatigue strength (σff) (n = 20 per group) were measured using piston‐on‐three‐balls method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Prause et al [ 57 ] also compared the flexural strength and Weibull modulus of 3D printed composite resins with milled composite resins and PICN for definitive restorations and found that the 3D printed composite resin exhibited the lowest biaxial flexural strength. Moreover, they also observed that the fracture origin of the 3D printed composite resin was correlated with the flaws introduced by the mixing procedure taking place during the 3D printing process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prause et al [ 57 ] also compared the flexural strength and Weibull modulus of 3D printed composite resins with milled composite resins and PICN for definitive restorations and found that the 3D printed composite resin exhibited the lowest biaxial flexural strength. Moreover, they also observed that the fracture origin of the 3D printed composite resin was correlated with the flaws introduced by the mixing procedure taking place during the 3D printing process.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main disadvantages concerning printable resins is linked to their filler volume. It has been shown that a greater amount of filler might impair the resin’s flow during the building process, therefore increasing the risk of incorporating air bubbles or areas of non-homogenous microstructure, consequently impairing mechanical properties [ 57 ]. For this reason, the printable resins currently available on the market consist of a significantly smaller amount of filler (30–50 wt%) compared to the resins designed for subtractive manufacturing (80–85 wt%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, importantly, the filler size of this product is similar to that of microfilled composites, and the filler content remains lower than that of most flowable composites [36]. Since microfilled composites with low filler contents may exhibit low wear resistance and poor mechanical properties, further studies are warranted to evaluate the in vitro and clinical performance of these novel materials [37,38].…”
Section: Discussionmentioning
confidence: 97%